A REVISED METHOD FOR OBSERVING THE SAME NANNOFOSSIL SPECIMENS WITH SCANNING ELECTRON MICROSCOPE AND LIGHT MICROSCOPE (Rivista italiana di Paleontologia e Stratigrafia, 1989)
A new method for the observation of the same nannofossil specimens with scanning electron microscope and light microscope, involving the use of a grid, is described. This technique provides a complete analysis of the morphological diagnostic characteristics of calcareous nannofossils and other microfossils.